Types of Tax Concessions for Attracting Foreign Direct Investment in Free Economic Zones - Chang Woon Nam; Doina Maria Radulescu (Center for Economic Studies and ifo Institute (CESifo), 2004)
Not only transition countries but also a large number of developing (and developed) countries have established free economic zones (FEZs) with the aim of attracting foreign capital by providing tax incentives, creating employment opportunities and promoting exports as well as regional development. Major theoretical justifications for the establishment of such economic zones generally maintain that there are economies of scale in the development of land and in the provision of common services and utilities as well as external economies of agglomeration by having similar industries grouped together. One of the main characteristics of FEZs is the provision of generous tax investment promotion schemes solely allowed in this enclave. In general such measures include: (a) profit tax exemption, (b) free or accelerated depreciation, (c) investment tax allowance, (d) subsidy for investment costs, etc. The incentive e.ects of various tax concessions on firms' investment decisions can be compared on the basis of the net present value model. Without taxation, the net present value (NPV) is equal to the present value of future gross return, discounted at an appropriate interest rate less investment cost. An investment project is therefore considered to be profitable when the NPV is positive. After introducing the corporate income tax, the present value of the asset generated from an investment amounts to the sum of the present value of net return (gross return less taxes) and the tax savings, led by, for example, an incentive depreciation provision. In this study the theoretical approach is accompanied by a model simulation based on selected parameters.
Keywords: 330; tax concessions; free economic zone; investment decision; net present value